KARTKA Z DZIEJÓW ROSYJSKIEJ NAUKI PRAWA KARNEGO W XIX WIEKU. UCZEBNIK UGOŁOVNOGO PRAVA WŁODZIMIERZA SPASOWICZA (1829-1906) - Paszkowska, Marzenna (Zeszyty Prawnicze, 2017)
PAGE IN THE HISTORY OF RUSSIAN SCIENCE OF CRIMINAL LAW THE COURSE-BOOK ON CRIMINAL LAW BY WŁODZIMIERZ SPASOWICZ (1829-1906) Summary Włodzimierz Spasowicz (1829-1906) was a Pole from Belarus. He had many different professions; he was a journalist, a publisher, a profesor and an attorney. In 1863 he published first modern course-book on criminal law in the history of Russia (Petersburg). On its basis, on the 22nd of December 1863, he got his PhD degree. In Petersburg liberal circles Spasowicz’s course-book received a positive review. The author’s aversion towards treating criminal law as a tool of deterring people, was underlined. Moreover, he demanded suppression of capital punishment and confiscation of property. However, the authorities of tsarist Russia led to the withdrawal of the course-book from the list of didactic aids and deprived Spasowicz of the right to give lectures at Russian universities (1864). The publication of criminal law course-book by Spasowicz meant progress in the development of Russian criminal law. Its role was underlined by such „great” professors of criminal law as N. Tagancew and I. Fojnicki.